2023
DOI: 10.1002/jaba.983
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of problem behavior: A 40‐year review

Abstract: Extensive reviews of functional analysis literature were conducted 10 (Beavers et al., 2013) and 20 (Hanley et al., 2003) years ago; we expanded this review to capture the vast and innovative functional analysis research that has occurred over the past decade. Our review produced 1,333 functional analysis outcomes from 326 studies on the functional analysis of problem behavior between June 2012 and May 2022. Some characteristics of functional analysis studies were similar across the current and previous two re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
37
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 132 publications
(274 reference statements)
2
37
0
1
Order By: Relevance
“…The current report demonstrated focused ABA methods of FA and behavioral treatment of pica in an outpatient, clinical psychology context. Evidenced-based ABA services have improved health, well-being, developmental, and behavioral challenges across diverse populations and problems (see LeBlanc et al, 2020; Melanson & Fahmie, 2023). Accordingly, children with SCD may also benefit from access to comprehensive ABA services such as early intensive behavioral intervention (EIBI; Smith & Iadarola, 2015) to address developmental concerns.…”
Section: Discussionmentioning
confidence: 99%
“…The current report demonstrated focused ABA methods of FA and behavioral treatment of pica in an outpatient, clinical psychology context. Evidenced-based ABA services have improved health, well-being, developmental, and behavioral challenges across diverse populations and problems (see LeBlanc et al, 2020; Melanson & Fahmie, 2023). Accordingly, children with SCD may also benefit from access to comprehensive ABA services such as early intensive behavioral intervention (EIBI; Smith & Iadarola, 2015) to address developmental concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Although improving the feasibility and precision are often conflicting goals, within‐session analyses are unique in their ability to facilitate progress in both directions. See Vollmer et al (1993), Jessel et al (2018), and Melanson and Fahmie (2023) for parallel discussions related to the functional analysis of challenging behavior. Our within‐session analyses were effective at identifying the most social and the most avoidant participants, but one limitation was that they did not allow for clear conclusions for participants displaying more moderate time allocation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a retrospective CCCS of FA outcomes over a 14-year period in a severe behavior clinic found that in 47.4% of cases, problem behavior was maintained by multiple sources of social reinforcement (Weber et al, 2023). This increase in the prevalence of multiply maintained problem behavior may, in part, be because of clinicians more frequently assessing multiple topographies in FAs (Beavers & Iwata, 2011; Melanson & Fahmie, 2023). The assessment of multiple topographies in the FA may also explain the higher prevalence of multiple maintained problem behavior we observed in the current study.…”
Section: Discussionmentioning
confidence: 99%